2016
DOI: 10.1177/0095244316653263
|View full text |Cite
|
Sign up to set email alerts
|

Castor oil-based polyurethane nanocomposites reinforced with organically modified clay

Abstract: Polyurethane(PU) nanocomposites were prepared using high shear mixing from castor oil, 4,4 0 -diphenylmethane diisocyanate, and modified clay (Closite 30B) as filler. The synthesis was carried out in bulk and without catalyst in the presence of clay. The clay percentage was varied from 1% to 5% by weight of the nanocomposite. The prepared nanocomposites were characterized using transmission electron microscopy (TEM), scanning electron microscopy, wide angle X-ray diffraction (WAXD), Fourier transform infrared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Figure 2 shows the FTIR spectra of Castor (a) and Reference (b) oil; each signal on the image shows its corresponding functional group. In the Castor oil spectrum (Figure 2a), the presented peaks coincide with those of reference spectrums for Castor Oil [16]. One of the most important signals that distinguish it from others vegetable oils is the broad peak at 3406 cm −1 that corresponds to the hydroxyl group (O-H) of the ricinoleic fatty acid.…”
Section: Chemical Characterizationsupporting
confidence: 58%
See 1 more Smart Citation
“…Figure 2 shows the FTIR spectra of Castor (a) and Reference (b) oil; each signal on the image shows its corresponding functional group. In the Castor oil spectrum (Figure 2a), the presented peaks coincide with those of reference spectrums for Castor Oil [16]. One of the most important signals that distinguish it from others vegetable oils is the broad peak at 3406 cm −1 that corresponds to the hydroxyl group (O-H) of the ricinoleic fatty acid.…”
Section: Chemical Characterizationsupporting
confidence: 58%
“…Castor oil is a triglyceride and consists principally of esters of ricinoleic fatty acid [5,16]. On the other hand, the commercial oil employed in this investigation as a reference is a fully-formulated oil that consists mainly of mineral base stock, chlorinated paraffins, and additives.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…It was observed that with increasing castor oil content into PUF composition rigidity increased. However, PUF derived from unmodified CO has a relatively low modulus, low thermal stability, and low flame‐retardant properties high curing time due to a secondary hydroxyl group and needs further modification . Recently, Hejna et al .…”
Section: Plant Oil Based Polyurethane Foammentioning
confidence: 99%
“…However, PUF derived from unmodified CO has a relatively low modulus, low thermal stability, and low flame-retardant properties high curing time due to a secondary hydroxyl group and needs further modification. [90][91][92] Recently, Hejna et al [93] reported a synthesis route for developing high hydroxyl content castor oil using transesterification with crude glycerol and the fabricated PUF showed better mechanical and thermal properties. Wang et al [94] synthesized PUF using blend polyol of CO and PEG.…”
Section: Castor Oil Based Polyurethane Foammentioning
confidence: 99%